MR‐guided simulation is superior than FDG/PET‐guided simulation for local control in nasopharyngeal cancer patients treated with intensity‐modulated radiotherapy. Issue 1 (10th August 2020) - Gundog, Mete; Basaran, Hatice; Dogan, Serap; Abdulrezzak, Ummuhan
Abstract: Background: MRI and PET/CT scans are the main supportive methods for nasopharyngeal cancer (NPC) for staging and planning. The aim of this study is to compare MRI and PET/CT scanning in terms of survival in patients with NPC who had MRI or PET/CT‐simulated radiotherapy planning. Methods: Pathological diagnosed nonkeratinized undifferentiated type and stage II‐IVA 91 NPC patients with treated intensity‐modulated radiotherapy plus chemotherapy were scanned. The patients were immobilized by a customized thermoplastic mask for fusion images both MRI scans and PET/CT scans. CTVs were created via MR‐guided simulation and PET/CT‐guided simulation. Results: PET/CT‐guided simulation was performed with 44 patients (56.4%) and MR‐guided simulation was performed with 34 patients (43.6%). Local recurrence‐free survival (LRFS) of patients was 68.1 months. LRFS of patients with PET/CT‐guided simulation was 59.9, while LRFS of patients with MR‐guided was 66.9 months. There was a statistically significant difference between groups ( P = .03). In the subgroup analyses, the patients were assessed by dividing into the three groups for the T1‐T2 stage, T‐3 stage, and T‐4 stage. In the patients with T1‐T2 stage, 5‐year LRFS rates were found %74.4 for PET/CT‐guided simulation and %83.3 for MR‐guided simulation. There was no statistically significant difference between groups ( P = .33). In the patients with T‐3 stage, 5‐year LRFS rates were found %55.6 for PET/CT‐guided simulation and %83.3 for MR‐guided simulation. There was not a statistically significant difference between groups ( P = .59). In the patients with T‐4 stage, 5‐year LRFS rates were found %42.2 for PET/CT‐guided simulation and %85.1 for MR‐guided simulation. The difference between groups was found to be statistically significant ( P = .04). Conclusion: In this study, we founded that MR‐guided simulation has better than PET/CT‐guided simulation for LRFS.